Chapter 7 Sandwich Generation in the Workplace – International Comparative Research - Dorota Kwiatkowska-Ciotucha; Urszula Załuska (Emerald Publishing Limited, 2022)
The chapter discusses the assumptions and main conclusions from the international comparative research, the key purpose of which was to identify and characterise the representatives of the sandwich generation (SG) in selected European countries in relation to professional activity. The research covered five countries, and when choosing them we took into account the diversity of welfare state models. The research was carried out in the autumn of 2020 with the use of a proprietary questionnaire on representative samples of Internet users aged 45–65 from Belgium (only Flanders), Finland, Italy, Poland and Great Britain. The conducted analyses confirmed the diversification of the situation of SG representatives in specific countries.
10.1108/978-1-80262-501-120221008; 10.1108/978-1-80262-501-120221008; Working Women in the Sandwich Generation: Theories, Tools and Recommendations for Supporting Women's Working Lives; EBP077208358